Contribution of the 3rd Century AH Musnad Book to the Historiography of Hadith - Ia Mufti Hidayat; Irwan Kurniawan; Engkos Kosasih; Muhammad Al Mighwar (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study explores the musnad books in the Islamic hadith tradition, the methodology of compiling musnad books, the richness of Hadith and information from the companions contained therein, and their contribution to the historiography of hadith with a focus on the third century Hijri era. The focus of the research is on the differences between musnad books and other hadith books, the methodology of compiling musnad books in the third century Hijri and the contribution of musnad books in the third century Hijri to historiography. This study uses a qualitative approach with a descriptive-analytical method to uncover the meaning and contribution of musnad books in the third century Hijri. The results of the study showed that the musnad books in the third century Hijri, with their compilation methodology that focuses on sanad and credibility of narration, have made significant contributions to the historiography of hadith, in the form of preservation and dissemination of hadith, reconstruction of the history of hadith narration, identification of narrators and hadith schools, and understanding the development of Islamic civilization in the early days. This research is expected to provide a clear and in-depth picture of the role and monumental contribution of the Musnad books in the development of Hadith science, enriching religious knowledge, and strengthening the faith of Muslims.